Strategic Diversification in Action: Amul’s Sweets and Gourmet Offerings - Zeel Modi; Pramith U Don; Mahendra D. Gurjar (Archives of Current Research International, 2025)
The present study explores the strategic diversification and product innovation undertaken by Gujarat Dairy Cooperatives, with a particular focus on GCMMF and its flagship brand, Amul, in the sweets (Mithai) and gourmet product segments. Traditionally known for dairy staples such as milk, butter, and ghee, Amul has successfully expanded its portfolio to include culturally significant Indian sweets and modern gourmet offerings like frozen pizzas, parathas, and snack foods. This research adopts a descriptive methodology, relying on secondary data to analyze product variety, packaging formats, shelf life, and distribution channels across general and modern trade. The study also examines consumer perceptions, market responsiveness, and the brand’s ability to blend tradition with convenience, health trends, and food safety standards. The findings reveal that Amul’s diversified product strategy has allowed it to cater to evolving consumer preferences, maintain cultural relevance, and reinforce its status as India’s most comprehensive food brand. The study concludes that the Gujarat Dairy Cooperative model offers valuable insights into sustainable brand evolution and market expansion within the Indian FMCG sector.